Mass balance study of an integrated phytoremediation system using different types of constructed wetlands for chromium removal - Sembada, Anca Awal; Theda, Yohanes (Asia-Pacific Journal of Science and Technology, 2024)
Phytoremediation is a biological waste treatment technique with highly promising prospects compared to other treatment systems. Constructed wetlands are one of the most widely applied phytoremediation methods. This study aimed to evaluate the phytoremediation process of chromium (Cr) using an integrated phytoremediation system. In this study, three different constructed wetland systems-free-floating, vertical subsurface flow, and horizontal subsurface flow-were used in sequence with three different plant species-Eicchornia crassipes, Typha augustifolia, and Catharanthus roseus. Each system had a residence time of three days. The Cr concentration used as the initial input was 0.5 mg/g. C. roseus had the highest bioconcentration factor (0.44±0.03) and translocation factor (1.27 ± 0.24) when compared to other species (p < 0.05). This integrated system had an overall process efficiency for Cr removal of 73.8 ± 1.07%. Based on this study, the integrated system is confirmed to have the potential for the removal of Cr from contaminated water when using these three plants and the further development of this integrated system on a larger scale is recommended.